2003
DOI: 10.1097/01.wcb.0000089600.87125.ad
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage to the Endoplasmic Reticulum is Implicated in Ischemic Neuronal Cell Death

Abstract: Summary:The endoplasmic reticulum (ER), which plays important roles in apoptosis, is susceptible to oxidative stress. Because reactive oxygen species (ROS) are robustly produced in the ischemic brain, ER damage by ROS may be implicated in ischemic neuronal cell death. We induced global brain ischemia on wild-type and copper/zinc superoxide dismutase (SOD1) transgenic rats and compared ER stress and neuronal damage. Phosphorylated forms of eukaryotic initiation factor 2␣ (eIF2␣) and RNA-dependent protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 60 publications
4
94
1
Order By: Relevance
“…In contrast, superoxide is known to instantly react with nitric oxide to form peroxynitrite, which can directly nitrosylate protein and impair protein function (Beckman and Crow, 1993). We recently demonstrated nitrosylated protein in ER fractions of rat brain proteins obtained from transient global cerebral ischemia (Hayashi et al, 2003b), which supports the role of ROS in ER damage.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, superoxide is known to instantly react with nitric oxide to form peroxynitrite, which can directly nitrosylate protein and impair protein function (Beckman and Crow, 1993). We recently demonstrated nitrosylated protein in ER fractions of rat brain proteins obtained from transient global cerebral ischemia (Hayashi et al, 2003b), which supports the role of ROS in ER damage.…”
Section: Discussionmentioning
confidence: 67%
“…Its content responses to speed and intensity of lipid peroxidation, it indirectly responds to the damage degree of free radical. Furthermore, we detected 4-hydroxynonenal (HNE) production in hippocampus which is produced when superoxide peroxidates arachidonic acid in the lipid bilayer, and is a well-known oxidative stress marker (Hayashi et al, 2003). Analysis of AD brains demonstrates an increase in free HNE in amygdala, hippocampus, and parahippocampal gyrus of the AD brain compared with age-matched controls (Markesbery et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, keeping cells in a reducing condition with DTT weakens such a possibility. An opposite mechanism can also be hypothesized, where oxidative stress or mitochondrial damage can lead to the generation of ER stress [43][44][45]. It has also been suggested that mitochondria play a role in ER stress and ER-induced apoptosis [46][47][48].…”
Section: Discussionmentioning
confidence: 99%